Molecular characterization of Apis mellifera colonies from Argentina: genotypic admixture associated with ecoclimatic regions and apicultural activities - Agra, Marcelo Nicolás (2018)
The European honeybee, Apis mellifera L. (Hymenoptera: Apidae), is considered as a main contributor to pollination of important crops and to honey production. Originally, beekeeping in Argentina was performed in an extended area covering the north and central region of the country and involving A. mellifera of European origin. Later, honeybees of African origin entered South America through Brazil and hybridized with European genetic resources, giving rise to Africanized populations that are characterized by a more aggressive behavior among other unfavorable traits. In this study, a genetic characterization of 396 honeybee colonies from the most important apicultural region of Argentina is presented in order to provide an updated description of population structure and genetic diversity of commercial and feral colonies. Diversity was analyzed using mitochondrial (COI‐COII region) and nuclear (eight microsatellites) markers. Three European (M4, C1, C2J) and three African (A1, A4, A30) haplotypes were detected. European haplotypes were mostly found in commercial apiaries, whereas African haplotypes were detected at high frequencies in feral colonies. Microsatellite data were analyzed to estimate population genetic variability at the province level and to evaluate genetic admixture. A high level of hybridization between Africanized and European honeybees was detected with a significant latitudinal cline from north to south. Extensive population admixture resulted in the definition of four clusters that included both feral and commercial colonies and that are explained not only by geographical distribution and degree of Africanization but also by human influence through beekeeping activities.